2006
DOI: 10.1002/bip.20649
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the β‐turn segment in designed peptide β‐hairpins: Construction of a stable type I′ β‐turn nucleus and hairpin–helix transition promoting segments

Abstract: Designed octapeptides Boc-Leu-Val-Val-Aib-(D)Xxx-Leu-Val-Val-OMe ((D)Xxx = (D)Ala, 3a;(D)Val, 3c and (D)Pro, 5a) and Boc-Leu-Phe-Val-Aib-(D)Ala-Leu-Phe-Val-OMe (3b) have been investigated to construct models of a stable type I' beta-turn nucleated hairpin and to generate systems for investigating helix-hairpin conformational transitions. Peptide 5a, which contains a central Aib-(D)Pro segment, is shown to adopt a stable type I' beta-turn nucleated hairpin structure, stabilized by four cross-strand hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…1) in which Pro 12 -Asn 13 was replaced with D-Pro-Gly (peptide 2 ), Aib-Gly (peptide 3 ), or δ-linked Orn (peptide 4 ). In terms of known folding behavior, D-Pro-Gly tends to nucleate type II’ or type I’ turns, [22] Aib-Gly is more diverse in its conformational preferences, [23] and δ 2 -Orn promotes a backbone reversal similar to that formed by D-Pro-Gly. [24] …”
Section: Resultsmentioning
confidence: 99%
“…1) in which Pro 12 -Asn 13 was replaced with D-Pro-Gly (peptide 2 ), Aib-Gly (peptide 3 ), or δ-linked Orn (peptide 4 ). In terms of known folding behavior, D-Pro-Gly tends to nucleate type II’ or type I’ turns, [22] Aib-Gly is more diverse in its conformational preferences, [23] and δ 2 -Orn promotes a backbone reversal similar to that formed by D-Pro-Gly. [24] …”
Section: Resultsmentioning
confidence: 99%
“…19 In addition, Balaram et al have designed b-hairpin peptides in which the central D-Pro-Xaa segment (Xaa 5 Gly, [20][21][22][23] Ala, 22,24 Aib, 22,24 L-Pro, 23,24 and Ac 6 c 24 ; Ac 6 c 5 1-aminocyclohexane-1-carboxylic acid) adopts a type II 0 b-turn in crystals. Balaram et al also designed b-hairpin peptides in which the central Aib-Xaa segment (Xaa 5 Gly, 25 D-Ala, 26,27 and D-Pro, 27,28 ) adopts type I 0 or II 0 b-turns in solution and in crystals. In addition, Masterson et al confirmed the formation of a bhairpin structure by a dodecapeptide in which the central Aib-D-Ala segment adopted a type I 0 b-turn in aqueous solution; this b-hairpin structure was superimposable on the corresponding b-hairpin structure containing the DPro-Gly segment.…”
mentioning
confidence: 97%
“…ß-Hairpin conformations have been successfully stabilized in linear peptides by exploiting tryptophan zipper motifs (π-π-stacking interactions between cross-ß-strand tryptophans at NHB positions), and related interactions (Eidenschink et al 2009;Russell et al 2002;Wu et al 2010b). The residues in the turn region have a strong infl uence upon ß-hairpin (Raghavender et al 2010;Rai et al 2007), which match the preferred right-handed twist of a hairpin. Other building blocks have been incorporated into turn regions and into the ß-strand regions, including, for example, the 1,2-dihydro-3(6H)-pyridinyl unit that favors extended conformations .…”
Section: ß-Hairpin Mimeticsmentioning
confidence: 99%